2017
DOI: 10.1016/j.jecr.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Cushing disease in a patient with multiple endocrine neoplasia type 2B

Abstract: Context Multiple endocrine neoplasia type 2B (MEN2B) is a rare autosomal-dominant cancer syndrome characterized in part by metastatic medullary thyroid cancer (MTC) and pheochromocytoma. Cushing disease is a rare cause of endogenous hypercortisolism in children. Case Description We describe a 21-year-old African-American male who was diagnosed at age 10 with an ACTH-secreting pituitary microadenoma. At age 16 he developed medullary thyroid cancer and was found to have multiple endocrine neoplasia type 2B wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…To date, only 2 cases of CD in patients with MEN2 syndrome have been reported: a case in an adult patient with MEN2A and one in a paediatric patient with MEN2B syndrome. In both cases, CD was caused by a microcorticotropinoma …”
Section: Introductionmentioning
confidence: 92%
“…To date, only 2 cases of CD in patients with MEN2 syndrome have been reported: a case in an adult patient with MEN2A and one in a paediatric patient with MEN2B syndrome. In both cases, CD was caused by a microcorticotropinoma …”
Section: Introductionmentioning
confidence: 92%
“…Three patients presented with an MEN2A-like phenotype; the fourth patient presented as MEN2B; among them, two CD cases have been associated with RET mutations. 9396 Other patients with similar phenotypes have been described in the literature, although genetic testing was not available or was negative for RET mutations. 97 Although rarely, MEN4 patients can also develop CS due to ectopic ACTH secretion from MTC.…”
Section: Genetic Alterations In Cushing’s Diseasementioning
confidence: 83%
“…Cushing disease has been reported in MEN4 due to a heterozygous 19-bp duplication (c.59_77dup19) in CDKN1B , leading to a truncated protein (Georgitsi et al 2007). It should be noted that corticotropinomas are also observed in MEN1 (Verges, et al 2002; Stratakis et al 2010;), and very rarely in MEN2B (Kasturi, et al 2017). Interestingly, one study found the common CDKN1B rs2066827 polymorphism to play a role in corticotropinoma susceptibility and tumorigenesis through a yet unidentified mechanism or, maybe, epigenetic factors (Sekiya, et al 2014).…”
Section: Clinical Manifestations Of Men4mentioning
confidence: 97%